Odpowiedź :
1]
[tex](4-x)(2+x)=0\\\\4-x=0 \ \vee \ 2+x=0\\\\x=4 \ \vee \ x=-2[/tex]
2]
[tex]5x(x+5)=0\\\\5x=0 \ \vee \ x+5=0\\\\x=0 \ \vee \ x=-5[/tex]
3]
[tex]7-x=6,5\\\\-x=6,5-7\\\\-x=-0,5 \ \ |:(-1)\\\\x=0,5[/tex]
1)
[tex](4-x)(2+x)=0\\8+4x-2x-x^2=0\\-x^2+2x+8=0\\\Delta=2^2-4*(-1)*8\\\Delta=4+32\\\Delta=36\\\sqrt{\Delta}=6\\x_1=\frac{-2-6}{-2}=\frac{-8}{-2}=4\\x_2=\frac{-2+6}{-2}=\frac{4}{-2}=-2\\[/tex]
2)
[tex]5x(x+5)=0\\5x = 0\\x_1 = 0\\\\x+5=0\\x_2=-5[/tex]
3)
[tex]7-x=6,5\\7-6,5=x\\0,5=x[/tex]